Spatial distribution of bolls affects yield formation in different genotypes of Bt cotton varieties - Jun-jun NIE; Yan-chao YUAN; Du-lin QIN; Yan-hui LIU; Shuang-lei WANG; Jin-pu LI; Mei-ling ZHANG; Na ZHAO; Wen-jun GUO; Jie QI; Li-li MAO; Xian-liang SONG; et al. (Journal of Integrative Agriculture)
To optimize the spatial distribution of cotton bolls and to increase the yield, the relationship between yield components and boll spatial distribution was investigated among different Bt (Bacillus thuringensis) cotton varieties. A five-year field experiment was conducted to reveal the reasons for the differences in lint yield and fiber quality across three Bt cotton varieties with different yield formations from 2013 to 2017. The lint yield of Jiman 169 (the average yield from 2013–2017 was 42.2 g/plant) was the highest, i.e., 16.3 and 36.9% higher than Lumianyan 21 (L21) and Daizimian 99B (99B), respectively. And the differences in boll weight among the three cultivars were similar to the lint yield, while the others yield components were not. So the increase in lint yield was mainly attributed to the enlargement in boll weight. However, the change in fiber quality was inconsistent with the lint yield, and the quality of L21 was significantly better than that of Jimian 169 (J169) and 99B, which was caused by the diversity of boll spatial distribution. Compared with 99B, the loose-type J169 had the highest number of large bolls in inner positions; the tight-type L21 had a few large bolls and the highest number of lower and middle bolls. And approximately 80.72% of the lint yield was concentrated on the inner nodes in Jiman 169, compared with 77.44% of L21 and 66.73% of 99B during the five-year experiment. Although lint yield was significantly affected by the interannual changes, the lint yield of J169 was the highest and the most stable, as well as its yield components. These observations demonstrated the increase in lint yield was due to the increase in boll weight, and the large bolls and high fiber quality were attributed to the optimal distribution of bolls within the canopies.